Managers Productivity Language Method and Qualitative Management Standards (QlMS) in Healthcare Campus Organization - Danino, Efrat; Kremer, Michal Asaf (Journal of Leadership, Accountability and Ethics, 2021)
Qualitative Management Standards (QlMS) is a representative title for the novel methodology that was created during the organizational development process at the Shamir Academic Campus during 2019-2020. QlMS consolidates by Dr. Danino the Academic Campus manager and a specialist in Healthcare systems and Dr. Asaf Kremer an expert consultant for organizational development (OD), the creator of the MPL (Managers Productivity Language) methods for Excellency in leadership, which are being implemented among leading organizations in Israel. The OD process was conducted using Managers Productivity Language guidelines, and tailored towards the campus urgent needs, considering the campus vision as well as the leadership team associated with it. This article addresses three main subjects: Part 1: Introduction: MPL- The rationale for the campus organizational development program. Part 2: The process: A description of the multidimensional organizational development process. Part 3: QMS: The novel approach that was developed during the Organizational Development process, which is referred to as “QlMS” in this article, which improves action in qualitative and quantitative terms in the health system.